2020
DOI: 10.1186/s13018-020-02137-z
|View full text |Cite
|
Sign up to set email alerts
|

Gradual ulnar lengthening in Masada type I/IIb deformity in patients with hereditary multiple osteochondromas: a retrospective study with a mean follow-up of 4.2 years

Abstract: Background Gradual ulnar lengthening is the most commonly used procedure in the treatment of Masada type I/II deformity in patients with hereditary multiple osteochondromas. However, the treatment remains controversial for the recurrence of deformity in growing children. This study aims to evaluate the clinical and radiological outcomes of ulnar gradual lengthening in our clinic. Methods We retrospectively reviewed patients who underwent ulnar leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…For ulnar lengthening in all eight patients, we used a monorail fixator. This is in line with the techniques proposed by Masada et al and two other studies [4] , [6] , [19] . The use of the uniplanar system has disadvantages in maintaining the direction of the distraction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For ulnar lengthening in all eight patients, we used a monorail fixator. This is in line with the techniques proposed by Masada et al and two other studies [4] , [6] , [19] . The use of the uniplanar system has disadvantages in maintaining the direction of the distraction.…”
Section: Discussionsupporting
confidence: 92%
“…This research sample is the same as the case series that is being presented. They concluded that tumor resection accompanied by gradual ulnar lengthening was the right measure to correct forearm deformities that have implications for the return of normal forearm function [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Chomiak et al [15] reported three out of 28 MHE patients with radial head dislocation who were treated with UL, but none of the radial heads became reduced. The same failure of which dislocated radial head did not achieve concentric reduction was seen in seven forearms using ulnar osteotomy and monolateral external fixator gradual lenthening, reported by Li et al [14] Dislocated radial head in MHE can be reduced through gradual UL with Ilizarov frame with a certain intervention to the radius. [11][12][13]26] It is considered earlier that the traction force to pull down the radial head may come from either the forearm interosseous membrane or a transfixation wire through DRUJ.…”
Section: Discussionsupporting
confidence: 60%
“…External fixators seem to be the current tendency in orthopedics, which indicates an optimistic application in forearm deformities. [8,[11][12][13][14][15][16]27] The device enables gradual, progressive, and controlled reduction of the forearm, as well as the elbow joint, and avoids excessive soft tissue interruption as well as widespread scarring. Besides, our novel hinge positioning, which is based on the expectant length and angulation of the ulna, provides adequate and balanced traction through the ring fixators and averts limiting the motion of the elbow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation